Honey Bee Suppresses the Parasitic Mite Vitellogenin by Antimicrobial Peptide - Wu, Yunfei; Liu, Qiushi; Weiss, Benjamin; Kaltenpoth, Martin; Kadowaki, Tatsuhiko (Frontiers in Microbiology, 2020)
The negative effects of honey bee parasitic mites and deformed wing virus (DWV) on honey bee and colony health have been well characterized. However, the relationship between DWV and mites, particularly viral replication inside the mites, remains unclear. Furthermore, the physiological outcomes of honey bee immune responses stimulated by DWV and the mite to the host (honey bee) and perhaps the pathogen/parasite (DWV/mite) are not yet understood. To answer these questions, we studied the tripartite interactions between the honey bee, Tropilaelaps mercedesae, and DWV as the model. T. mercedesae functioned as a vector for DWV without supporting active viral replication. Thus, DWV negligibly affected mite fitness. Mite infestation induced mRNA expression of antimicrobial peptides (AMPs), Defensin-1 and Hymenoptaecin, which correlated with DWV copy number in honey bee pupae and mite feeding, respectively. Feeding T. mercedesae with fruit fly S2 cells heterologously expressing honey bee Hymenoptaecin significantly downregulated mite Vitellogenin expression, indicating that the honey bee AMP manipulates mite reproduction upon feeding on bee. Our results provide insights into the mechanism of DWV transmission by the honey bee parasitic mite to the host, and the novel role of AMP in defending against mite infestation.